The Control Environment, Employee Fraud and Counterproductive Workplace Behaviour: An Empirical Analysis - Zauwiyah, Ahmad; Mariati, Norhashim (2008)
The increasing use of technology for both productive and managerial business functions raises new issues related to fraud and internal control. Fraud is on an increasing trend and if left unchecked can cause significant losses to employers. This study therefore investigates the relationship between employees' attitudes toward fraudulent behaviours at workplace and the control environment. A sample 433 employees in Malaysia were involved in this empirical study. Data was gathered via a self-administered questionnaire survey. Results of the regression analyses performed identify elements of the control environment that could influence employees' attitudes towards employee fraud and thus highlight elements that should receive more attention. Ultimately, an organization must put in place an information system that can detect fraudulent behaviours and at the same time develop the right control environment that can prevent fraudulent activities.